2023
DOI: 10.3390/app13042145
|View full text |Cite
|
Sign up to set email alerts
|

Hatchability and Survival of Lamproglena clariae Fryer, 1956 Exposed to Increasing Concentrations of Aqueous Aluminium

Abstract: The effect of increased aluminium concentration on the hatchability and survival of Lamproglena clariae is unknown. During October 2019 and October 2020, infected C. gariepinus were collected from the Vaal River and transferred to a controlled aquarium room. Parasite infection was established on acclimated C. gariepinus. Adult female parasites (F2 and F3 generation) on live fish were inspected for egg strings. Viable egg strings were removed, leaving females attached to produce more eggs. Bioassays were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Furthermore, for another crustacean Lamproglena clariae , it was observed that exposure to metals resulted in a change to their metalloprotein expression (Ndaba et al 2022 ) and a reduction in infection intensity in natural environments (Tsotetsi et al 2004 ; Crafford and Avenant-Oldewage 2009 ; Pretorius and Avenant-Oldewage 2021 ). All previous studies have focused on attached adult female L. clariae (Ndaba et al 2022 ; Pretorius and Avenant-Oldewage 2022 ). This can be attributed to the fact that only gravid female L. clariae parasitise the host fish, while all other life stages and adult males are free-living (Madanire-Moyo and Avenant-Oldewage 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, for another crustacean Lamproglena clariae , it was observed that exposure to metals resulted in a change to their metalloprotein expression (Ndaba et al 2022 ) and a reduction in infection intensity in natural environments (Tsotetsi et al 2004 ; Crafford and Avenant-Oldewage 2009 ; Pretorius and Avenant-Oldewage 2021 ). All previous studies have focused on attached adult female L. clariae (Ndaba et al 2022 ; Pretorius and Avenant-Oldewage 2022 ). This can be attributed to the fact that only gravid female L. clariae parasitise the host fish, while all other life stages and adult males are free-living (Madanire-Moyo and Avenant-Oldewage 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pretorius et al [2] reported that the hatchability and survival of Lamproglena clariae is negatively affected by increased concentrations of Al. By removing this ectoparasite from living fish, the need to kill the host organism is eliminated, underscoring the utility of L. clariae as a bioindicator of metal pollution.…”
mentioning
confidence: 99%